THE DYNAMICS OF ARCHIVE MANAGEMENT IN THE DIGITAL DISRUPTION ERA TO INFLUENCE EMPLOYEE PERFORMANCE THROUGH ORGANIZATIONAL BEHAVIOR AS A MEDIATOR - Lailatul Fitriyah Ella; Brillian Rosy (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2025)
Phenomenon/Issue: The digital disruption era compels public organizations to transform traditional archive management into digital formats, demanding readiness from both infrastructure and human resources. Purpose: This study aims to examine the impact of archive management on employee performance, the mediating role of organizational behavior, and the relationship dynamics in a public institution. Novelty: This research introduces organizational behavior as a mediating variable between digital archive management and employee performance within a public office context. Research Methods: A quantitative method was used, involving 53 respondents at the Surabaya City Library and Archives Office. Data were analyzed using SmartPLS 4. Results: Archive management positively and significantly influences both employee performance and organizational behavior. Organizational behavior also significantly affects performance and mediates the relationship between archive management and employee performance. Research Contributions: This study contributes to understanding the role of behavioral factors in implementing digital archive systems and offers practical strategies for performance improvement in public services.